FUNGSI DAN PERAN BISNIS RITEL DALAM SALURAN PEMASARAN - Tri Joko Utomo (STIE Pelita Nusantara Semarang, 2009)
Product that be produced must be sold to consumer or end user so that producer gets a financial profit. Producer leads their product to consumer use marketing line. Marketing line usually involves the other side: producer, middlemen, and end consumer or industrial user. There are many kinds of middlemen that can be used by producer to lead their product, one of them is retailer or retail business. Retail business can be classified based on measurement, possession, operational, etc. Even though marketing line can be classified in several levels according to the amount of the middlemen.Retail business has function as middlemen in marketing line and the function ininformation, promotion, negotiation, order, expenditure, risk taker, physical possession, payment and proprietary right. Retail business’s role in marketing line for producer snatch at product, fund, advertising and promotion, consumer, and competitor.